Industrial Policy Priorities of Russia in the Context of Challenges of the Fourth Industrial Revolution. Part 1 - Romanova, Olga Aleksandrovna (Economy of Regions, 2018)
We article proves that the industrial policy is not only an element coordinating the various types of state policies. It is as well a platform, on which the economic policy of the state is built. I systematize five directions representing the traditional approach to understanding the industrial policy and three new directions of its understanding. I emphasize that a new purpose of the industrial policy as the achievement of «an image» of a “good economy”, and that the «standard projects» of regional industrial policy are unacceptable. I define new characteristics of the Fourth Industrial Revolution. Its fundamental features are harmonization and integration of a large amount of research disciplines. ms, in turn, imposes high requirements to developing priorities for both the federal and regional industrial policy. Another feature of the Fourth Industrial Revolution is the emergence of the digital economy. I analyse its development in Russia as compared with the developed countries. Moreover, I systemize the studies about the readiness of Russian companies for the digital economy. Пє information and communication technologies are the most important factor for the digital economy. We analysis of these technologies development in regions showed high level of its differentiation of regional indicators (from 1.5 to more than 300 times). We assessment of the development of information and communication technologies allow categorise the Middle Urals as a leading region almost for all indicators in this area not only in the Ural Federal District, but also in Russia, in general. We importance of new business models as most essential innovations during the Fourth Industrial Revolution has increased. Wis defines new agents and objects of industrial policy. We results of the research may be used to correct the regional strategy of socio-economic development as well as laws on industrial policy.